Micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor rod and preparation method and construction method of micro-expansion early-strength cement-based grouting material
By optimizing the raw material ratio of cement-based grouting materials and adding composite admixtures, the problems of low early strength and complex construction of traditional anti-floating anchor materials have been solved, and a micro-expansion early-strength cement-based grouting material with high fluidity, strong adhesion and crack resistance has been achieved, thereby improving the durability and construction efficiency of anti-floating anchors.
Patent Information
- Application Number
- CN202510872442.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-09-09
AI Technical Summary
Traditional anti-floating anchor grouting materials have problems such as low early strength, easy cracking of the grouting body, insufficient adhesion and complex construction, which affect the durability and construction efficiency of the anchor.
Micro-expansion early-strength cement-based grouting materials are used. By optimizing the raw material ratio and adding composite admixtures, including powdered polycarboxylic acid water-reducing agent, defoaming agent, plastic expansion agent and rheological additive, a colloid with high shear-thinning properties is formed, ensuring high fluidity under low shear and high viscosity under static conditions, enhancing the bonding force between the anchor rod and the formation, and compensating for cement shrinkage through micro-expansion to improve crack resistance.
It achieves full filling of pores without slurry leakage, enhances the bonding strength between the anchor rod and the stratum, improves the pull-out bearing capacity, ensures the long-term stability and high cost-effectiveness of the anti-floating anchor rod, and meets the high standards of modern construction projects.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building materials, in particular to a micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor rods and a preparation method thereof, which is suitable for construction projects such as basements with high requirements for crack resistance and early strength. Background Art
[0002] With the continuous development of construction engineering, anti-floating anchor rods have been widely used in underground structural engineering, such as the anti-floating design of basements. The performance and quality of anti-floating anchor rods play a vital role in ensuring the safety and stability of building structures.
[0003] Traditional anti-floating anchor grouting materials have some defects and shortcomings. For example, the grouting body is prone to cracking, resulting in a decrease in anti-corrosion performance and affecting the durability of the anchor; during the construction process, the bonding force between the grouting body and the anchor is insufficient, affecting the pull-out bearing capacity of the anchor; and the grouting material has poor fluidity and pumpability, the construction operation is relatively complicated, and it is easy to have incomplete grouting.
[0004] Therefore, it is of great practical significance to develop a cement-based grouting material with excellent performance, convenient construction, and the ability to effectively improve the performance of anti-floating anchor rods. Summary of the Invention
[0005] To address the problems of low early strength in conventional cement-based grouting materials for anti-floating anchors and the tendency for the grout to shrink and crack during the curing process, resulting in a decrease in crack resistance and affecting the durability of the anchor, the present invention aims to propose a micro-expansion, early-strength cement-based grouting material suitable for prestressed anti-floating anchors, as well as its preparation and construction methods. By optimizing the raw material ratio, the colloid formed by this material exhibits extremely high shear-thinning properties, high viscosity under static and low-shear conditions, and high fluidity under dynamic conditions such as grouting. This material can fully fill the irregular pores between the anchor and the formation without slurry leakage, forming a uniform slurry layer, enhancing the adhesion between the anchor and the formation, and improving the pull-out bearing capacity. Furthermore, the material's micro-expansion compensates for cement shrinkage, and its excellent crack resistance ensures the long-term stability of the anti-floating anchor, meeting the high material performance standards of modern construction projects while achieving a low dosage and high cost-effectiveness.
[0006] The technical solution adopted in the present invention is as follows:
[0007] The invention discloses a micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor rods. The material comprises cement, fine aggregate, a composite admixture and water, wherein the mass ratio of the cement, fine aggregate, composite admixture and water is 1:(1-2):(0.00132-0.0027):0.35; the composite admixture is formed by mixing a powdered polycarboxylic acid water reducer, a defoaming agent, a plastic expansion agent and a rheological additive.
[0008] Furthermore, the composite admixture is formed by mixing the following components:
[0009] Powdered polycarboxylate water reducer, which accounts for 0.08%-0.15% of the total mass of the base material;
[0010] Defoaming agent, which accounts for 0.02%-0.05% of the total mass of the base material;
[0011] Plastic expansion agent, which accounts for 0.02%-0.05% of the total mass of the base material;
[0012] Rheological additives, which account for 0.012%-0.02% of the total mass of the base material;
[0013] The base material is a mixture of cement and fine aggregate.
[0014] In the above technical solution,
[0015] The mechanism by which the powdered polycarboxylate water-reducing agent in the composite admixture affects the performance of the grouting material is that the water-reducing agent is a surfactant, which has a wetting and dispersing effect on cement particles after being added, thereby reducing the unit water consumption and improving the fluidity of the slurry.
[0016] The defoamer in the composite admixture affects the properties of the grouting material by rapidly diffusing into the foam, reducing its local surface tension and causing it to break. Simultaneously, on the surface of the foam film, the defoamer droplets continue to spread and penetrate deeply, forming a bridging-stretching mechanism that ultimately thins and breaks the film.
[0017] The mechanism by which the plastic expansion agent in the composite admixture affects the properties of the grouting material is that upon contact with water in the cement slurry, the plastic expansion agent begins to react in an alkaline environment, causing the azo compound to decompose and produce nitrogen. After surface treatment, the bauxite mineral slowly hydrolyzes, releasing gas that increases the expansion rate of the grouting material through foaming.
[0018] The mechanism by which the rheological additive in the composite admixture affects the properties of the grouting material is that the rheological additive is composed of a nanosilicate material modified with microbial polysaccharides. The nanosilicate material has a lamellar structure that forms a "house of cards" structure in an aqueous system through ionic bonding and van der Waals forces. This structure significantly increases the base viscosity of the cement slurry and enhances its static stability. When shear forces (such as stirring and pumping) are applied, the house of cards structure is reversibly destroyed, and the silicate lamellae act as a lubricant, reducing viscosity and thus improving workability.
[0019] The composite admixture has the functionalities of water reduction, expansion, defoaming, water retention, thickening and the like.
[0020] The composite admixture has the characteristics of low dosage and high cost performance while ensuring excellent performance. The total dosage of the composite admixture is 0.132%-0.27% of the total mass of the base material.
[0021] Furthermore, the powdered polycarboxylate water reducer is 2260 type polycarboxylate water reducer.
[0022] Furthermore, the defoaming agent is a D608 modified silicone polyether defoaming agent.
[0023] Furthermore, the plastic expansion agent is an SP25 plastic expansion agent.
[0024] Furthermore, the rheological additive is RS-20 rheological additive.
[0025] In the above technical solution,
[0026] The four components of the composite admixture are commercially available. For example, the four components of the composite admixture can all be produced by Guangzhou Jiantubao Building Materials Co., Ltd., wherein type 2260, type D608, type SP25 and type RS-20 are all produced by the company.
[0027] The powdered polycarboxylic acid water-reducing agent in the composite admixture is type 2260, which has better effects than existing common water-reducing agents, with a water-reducing rate of not less than 25% and up to 40% or more. It has the advantages of low dosage, high water-reducing capacity and good cement-based adaptability, while the water-reducing rate of common water-reducing agents is generally 8%-13%.
[0028] The defoamer in the composite admixture is of the D608 modified silicone polyether type, whose aqueous solution is generally neutral or nearly neutral, and does not introduce corrosive ions, thus avoiding potential corrosion problems caused by extreme pH values. At the same time, the defoamer has a low dosage and excellent defoaming speed, stable chemical properties, and can improve the surface effect of the mortar and increase the density of the mortar.
[0029] The plastic expansion agent in the composite admixture adopts SP25 type, which has obvious early expansion, long expansion duration and the recommended dosage is only 0.02%-0.05% of the total mass of the base material.
[0030] The rheological additive in the composite admixture is RS-20 type, which has excellent water-locking properties. Fine particles in the slurry will not settle, segregation and bleeding are reduced, and the recommended dosage is only 0.01%-0.03% of the total mass of the base material.
[0031] Furthermore, the fine aggregate is 40-70 mesh machine-made sand. The reason for using machine-made sand as fine aggregate is that compared with natural sand such as river sand, the machine-made sand can significantly improve the wear resistance and compressive strength of the mortar.
[0032] Furthermore, the cement is P.O 42.5 ordinary Portland cement. The cement used is P.O 42.5 ordinary Portland cement produced by Shenda Building Materials Co., Ltd. The setting time of this P.O 42.5 ordinary Portland cement is: initial setting no earlier than 45 minutes, and final setting no later than 10 hours; the compressive strength is: 17.0 MPa at 3 days, and 42.5 MPa at 28 days.
[0033] The method for preparing a micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchors of the present invention comprises the following steps: uniformly mixing cement, fine aggregate, composite admixture and water in a predetermined proportion to form a grouting material.
[0034] The invention provides a construction method for a prestressed anti-floating anchor rod, which uses the micro-expansion early-strength cement-based grouting material for grouting to form a micro-expansion early-strength slurry layer to enhance the bonding force between the anchor rod and the stratum.
[0035] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0036] Compared to existing technologies, the grouting material of this invention exhibits micro-expansion and rheological properties, resulting in a colloid with extremely high shear-thinning properties. This material exhibits high viscosity under static and low-shear conditions, and regains its high fluidity under dynamic conditions such as grouting. This material can fully fill irregular pores between the anchor and the formation without slurry leakage, forming a uniform slurry layer, enhancing the bond between the anchor and the formation and improving its pull-out bearing capacity. Furthermore, the material's micro-expansion compensates for cement shrinkage, and its excellent crack resistance ensures the long-term stability of anti-floating anchors. This material not only meets the high material performance standards of modern construction projects, but also achieves high cost-effectiveness with low dosage. DETAILED DESCRIPTION
[0037] In order to better understand the purpose, technical solutions and advantages of the present invention, the following will be described in detail with reference to specific embodiments. It should be noted that these embodiments only represent a part of the many possible implementation methods of the present invention, and not all of them. The purpose of the following description is to clearly illustrate the technical solutions of the present invention, not to limit the scope of protection of the present invention. All equivalent transformations made within the scope of the claims of this application are within the scope of protection of the claims of this application.
[0038] Example 1
[0039] The present embodiment provides a micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchors, and its preparation method includes the following steps: using cement: fine aggregate: composite admixture: water in a mass ratio of 1:1:0.0017:0.35. The cement is PO 42.5 cement; the fine aggregate is machine-made sand with a mesh size of 40-70;
[0040] Among them, the composite admixture is mixed by the following components:
[0041] Powdered polycarboxylate water reducer, which accounts for 0.08% of the total mass of the base material;
[0042] Defoaming agent, which accounts for 0.02% of the total mass of the base material;
[0043] Plastic expansion agent, which accounts for 0.05% of the total mass of the base material;
[0044] Rheological additive, which accounts for 0.02% of the total mass of the base material;
[0045] The base material is a mixture of cement and fine aggregate.
[0046] The powdered polycarboxylic acid water-reducing agent is 2260 polycarboxylic acid water-reducing agent, the defoaming agent is D608 modified silicone polyether defoaming agent, the plastic expansion agent is SP25 plastic expansion agent, and the rheological additive is RS-20 rheological additive.
[0047] Example 2
[0048] With reference to Example 1, this Example 2 differs from Example 1 in that the composite admixture of this Example 2 is formed by mixing the following components:
[0049] Powdered polycarboxylate water reducer, which accounts for 0.1% of the total mass of the base material;
[0050] Defoaming agent, which accounts for 0.02% of the total mass of the base material;
[0051] Plastic expansion agent, which accounts for 0.03% of the total mass of the base material;
[0052] Rheological additive, which accounts for 0.02% of the total mass of the base material;
[0053] The base material is a mixture of cement and fine aggregate.
[0054] The rest is the same as Example 1.
[0055] Example 3
[0056] With reference to Example 1, this Example 3 is different from Example 1 in that the grouting material of this Example 3 is a mixture of cement, fine aggregate, composite admixture and water in a mass ratio of 1:1:0.0015:0.35.
[0057] The composite admixture of this embodiment 3 is formed by mixing the following components:
[0058] Powdered polycarboxylate water reducer, which accounts for 0.08% of the total mass of the base material;
[0059] Defoaming agent, which accounts for 0.02% of the total mass of the base material;
[0060] Plastic expansion agent, which accounts for 0.03% of the total mass of the base material;
[0061] Rheological additive, which accounts for 0.02% of the total mass of the base material;
[0062] The base material is a mixture of cement and fine aggregate.
[0063] The rest is the same as Example 1.
[0064] Grouting material performance testing methods for Examples 1-3: Cement, fine aggregate, composite admixture, and water were mixed and stirred uniformly in a proportioned mass ratio to form a slurry. Fluidity testing was performed in accordance with the "Technical Specification for the Application of Cement-Based Grouting Materials" (GB / T 50448-2015) and "Cement-Based Grouting Materials" (JC / T 986-2018). Cubes measuring 70.7 mm × 70.7 mm × 70.7 mm were prepared for compressive strength testing. Vertical expansion testing was performed in accordance with the "Technical Specification for the Application of Cement-Based Grouting Materials" (GB / T 50448-2015) and "Technical Specification for the Application of Concrete Admixtures" (GB50119-2013).
[0065] The test performance results of the grouting materials are shown in Table 1 below.
[0066] Table 1
[0067] Example Forming date Cement: Fine Aggregate: Composite Admixture: Water Flowability (mm) 3-day compressive strength (MPa) 3d vertical expansion rate (%) Example 1 2025.4.27 1:1:0.0017:0.35 324 31.4 1.354 Example 2 2025.4.27 1:1:0.0017:0.35 330 32.2 0.126 Example 3 2025.4.27 1:1:0.0015:0.35 332 33.3 0.107
[0068] According to the Technical Specifications for Application of Cement-based Grouting Materials (GB / T 50448-2015), the fluidity of the grouting material must be greater than 290 mm, the 3-day compressive strength must be greater than 30 MPa, and the 3d vertical expansion rate must meet the requirements of 0.1%-3.5%.
[0069] Examples 1-3 all meet the requirements of the specification. Example 3 has better fluidity and 3-day compressive strength than Examples 1 and 2, and has the advantages of low dosage and high cost performance.
[0070] Comparative Example 1
[0071] Referring to Example 1, the grouting material of this comparative example 1 is basically the same as that of Example 1, except that the grouting material of this comparative example 1 is mixed in a mass ratio of cement: fine aggregate: composite admixture: water of 1:1:0.00072:0.35.
[0072] The composite admixture of Comparative Example 1 does not use a defoamer, and is composed of the following components:
[0073] Powdered polycarboxylate water reducer, which accounts for 0.04% of the total mass of the base material;
[0074] Plastic expansion agent, which accounts for 0.02% of the total mass of the base material;
[0075] Rheological additive, which accounts for 0.012% of the total mass of the base material;
[0076] The base material is a mixture of cement and fine aggregate.
[0077] The rest is the same as Example 1.
[0078] Comparative Example 2
[0079] With reference to Example 1, the grouting material of Comparative Example 2 is substantially the same as that of Example 1, except that the grouting material of Comparative Example 2 is prepared by mixing cement, fine aggregate, composite admixture, and water in a mass ratio of 1:1:0.00122:0.35.
[0080] The composite admixture of Comparative Example 2 does not use a defoamer, but adds an early strength agent, which is mixed with the following components:
[0081] Powdered polycarboxylate water reducer, which accounts for 0.04% of the total mass of the base material;
[0082] Plastic expansion agent, which accounts for 0.02% of the total mass of the base material;
[0083] Rheological additive, which accounts for 0.012% of the total mass of the base material;
[0084] Early strength agent, which accounts for 0.05% of the total mass of the base material;
[0085] The base material is a mixture of cement and fine aggregate.
[0086] The rest is the same as Example 1.
[0087] Comparative Example 3
[0088] With reference to Example 1, the grouting material of Comparative Example 3 is substantially the same as that of Example 1, except that the grouting material of Comparative Example 3 is prepared by mixing cement, fine aggregate, composite admixture, and water in a mass ratio of 1:1:0.0014:0.35.
[0089] The composite admixture of Comparative Example 3 does not use a defoamer, and is composed of the following components:
[0090] Powdered polycarboxylate water reducer, which accounts for 0.1% of the total mass of the base material;
[0091] Plastic expansion agent, which accounts for 0.02% of the total mass of the base material;
[0092] Rheological additive, which accounts for 0.02% of the total mass of the base material;
[0093] The base material is a mixture of cement and fine aggregate.
[0094] The rest is the same as Example 1.
[0095] The test method for the fluidity performance of the grouting materials in Comparative Examples 1-3 is the same as that in Examples 1-3. The test results of the fluidity performance of the grouting materials in Comparative Examples 1-3 are shown in Table 2 below.
[0096] Table 2
[0097] Comparative Example Forming date Cement: Fine Aggregate: Composite Admixture: Water Flowability (mm) Comparative Example 1 2025.5.12 1:1:0.00072:0.35 115 Comparative Example 2 2025.5.12 1:1:0.00122:0.35 280 Comparative Example 3 2025.5.12 1:1:0.0014:0.35 330
[0098] Since the fluidity performance of the grouting materials in the above-mentioned comparative examples 1-2 does not meet the requirements of the specifications, too low fluidity will cause clogging of the grouting equipment, thereby affecting the pumpability. Therefore, the construction conditions are not met and construction cannot be carried out. Even if the compressive strength meets the requirements, it cannot be used. In view of the above phenomenon, no other performance tests are performed on the grouting materials in the above-mentioned comparative examples 1-2.
[0099] Since the fluidity performance of the grouting material in Comparative Example 3 meets the construction conditions, a 3-day compressive strength test and a 3d vertical expansion rate test were conducted on the grouting material in Comparative Example 3. The results are shown in Table 3 below.
[0100] Table 3
[0101] Comparative Example Forming date Cement: Fine Aggregate: Composite Admixture: Water 3-day compressive strength (Mpa) 3d vertical expansion rate (%) Comparative Example 3 2025.5.12 1:1:0.0014:0.35 20.7 -0.006
[0102] The 3-day compressive strength of the grouting material of Comparative Example 3 is 20.7 MPa, and the 3d vertical expansion rate is -0.006%, that is, the grouting material shrinks after curing. The above performances do not meet the requirements of the specification.
[0103] By comparison, it can be seen that the performance of the grouting material prepared in Example 3 is better than that of Comparative Examples 1 to 3, and meets the requirements of the specifications and construction conditions.
[0104] The grouting material described in Example 3 that meets the requirements of the specification was tested for setting time and compressive strength at full age. The results are shown in Table 4 below.
[0105] Table 4
[0106] Example Forming date Cement: Fine Aggregate: Composite Admixture: Water Flowability (mm) Initial setting time (min) Final setting time (min) 3-day compressive strength (MPa) 7-day compressive strength (MPa) 14-day compressive strength (MPa) 28-day compressive strength (MPa) 3d vertical expansion rate (%) Example 3 2025.5.30 1:1:0.0014:0.35 330 262 327 33.3 42.0 47.0 50.2 0.107
[0107] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchors, characterized in that: The invention is composed of cement, fine aggregate, composite admixture and water, wherein the mass ratio of cement, fine aggregate, composite admixture and water is 1:(1-2):(0.00132-0.0027):0.35; wherein the composite admixture is a mixture of powdered polycarboxylic acid water reducer, defoaming agent, plastic expansion agent and rheological additive.
2. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 1, characterized in that: The composite admixture is formed by mixing the following components: Powdered polycarboxylate water reducer, which accounts for 0.08%-0.15% of the total mass of the base material; Defoaming agent, which accounts for 0.02%-0.05% of the total mass of the base material; Plastic expansion agent, which accounts for 0.02%-0.05% of the total mass of the base material; Rheological additives, which account for 0.012%-0.02% of the total mass of the base material; The base material is a mixture of cement and fine aggregate.
3. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 2, characterized in that: The powdered polycarboxylate water reducer is 2260 type polycarboxylate water reducer.
4. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 2, characterized in that: The defoamer is a D608 modified silicone polyether defoamer.
5. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 2, characterized in that: The plastic expansion agent is an SP25 plastic expansion agent.
6. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 2, characterized in that: The rheological additive is RS-20 rheological additive.
7. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 1, characterized in that: The fine aggregate is 40-70 mesh machine-made sand.
8. The micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchor according to claim 1, characterized in that: The cement is P.0 42.5 ordinary Portland cement.
9. A method for preparing the micro-expansion early-strength cement-based grouting material suitable for prestressed anti-floating anchors according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing cement, fine aggregate, composite admixture and water in a predetermined proportion to form grouting material.
10. A construction method for prestressed anti-floating anchor rod, characterized in that: Grouting is performed using the micro-expansion early-strength cement-based grouting material according to any one of claims 1 to 8 to form a micro-expansion early-strength slurry layer to enhance the bonding force between the anchor rod and the stratum.
Citation Information
Cited By
Quick-setting early-strength anchor slurry as well as preparation method and application thereof
CN120923194A